Asian American identities, families, and schooling - Park, Clara C., 1944-; Goodwin, A. Lin; Lee, Stacey J., 1962- (Research on the education of Asian and Pacific Americans., 2003)
This anthology is the second volume in a series sponsored by the Special Interest Group-Research on the education of Asian and Pacific Americans (SIG-REAPA) of the American Educational Research Association and California Association for Asian and Pacific American Education. The series intends to be a national voice for the education of Asian and Pacific Americans, and provides an integral view of new knowledge in the field of Asian and Pacific American education from scholarly and educational practitioners' perspectives. The current collection includes research-based articles by junior and senior scholars in the field of Asian and American education. The articles highlight both the success and the continuing struggles of Asian American students, teachers, and families. Students, educational practitioners, and scholars will find this book to be an important resource.